Assessing the effective demand for improved water supply service in Malaysia - Zuraini Anang (United Kingdom: Newcastle University, 2013)
In Malaysia, the water management system was restructured in January 2005 by the transfer of water supplies and services from the State List to the Concurrent List. The National Water Services Commission or Suruhanjaya Perkhidmatan Air Negara (SPAN) was established in July 2006 as the technical and economic regulator for the improvement of water supply quality and the efficiency of the water industry. This study focuses on SAJ Holdings (SAJH). This water supply company provides a fully integrated service, i.e. it is involved in the all the processes of drinking water supply; these range from raw water acquisition, treatment and purification, and the subsequent distribution of purified water to customers, plus billing and payment collection.